Determinación de la susceptibilidad a la vancomicina en cepas de Staphylococcus aureus meticilino-resistente (SARM) aisladas en un hospital de tercer nivel de complejidad de Medellín mediante varias pruebas de sensibilidad antimicrobiana (2012)
ABSTRACT: Vancomycin has been the most effective antibiotic against infections caused by methicillin resistant Staphylococcus aureus (MRSA). To date there are no reports of Intermediate Vancomycin-Intermediate Staphylococcus aureus (VISA) or Vancomycin-Resistant Staphylococcus aureus (VRSA) in Colombia; however there is a high prevalence of MRSA and increased vancomycin use, which are contributing factors to their emergence. Additionally, routine methods used for detection of these strains such as automated and disc diffusion have limitations. OBJECTIVE To evaluate vancomycin susceptibility in a collection of MRSA strains isolated from patients between 2008-2010 in a University hospital of Medellin. MATERIALS AND METHODS 150 MRSA isolates were selected. The vancomycin minimum inhibitory concentration (MIC) was performed by Vitek-2 and Etest. Additionally, vancomycin screen agar plates were employed. RESULTS All of the isolates tested were susceptible to vancomycin, however, differences between the evaluated methods were observed: the 59.3% of the isolates (n = 89) showed an MIC ≤ 1 µg/mL by Etest, whereas by Vitek2, only the 22% (n = 33) of the isolates had this value. CONCLUSIONS We found a significant number of isolates with an MIC ≤ 1 µg/mL, which have been associated with increased risk of treatment failure. These results show the relevance of permanent surveillance of antibiotic resistance, to achieve the establishment of appropriate control strategies. comycin has been the most effective antibiotic against infections caused by methicillin resistant Staphylococcus aureus (MRSA). To date there are no reports of Intermediate Vancomycin-Intermediate Staphylococcus aureus (VISA) or Vancomycin-Resistant Staphylococcus aureus (VRSA) in Colombia; however there is a high prevalence of MRSA and increased vancomycin use, which are contributing factors to their emergence. Additionally, routine methods used for detection of these strains such as automated and disc diffusion have limitations. Key words: Antimicrobial Susceptibility Testing. Methicillin-resistant Staphylococcus aureus (MRSA). Resistance. Vancomycin.